Ind2TiMe2‐catalyzed addition of methyl‐ and ethylamine to alkynes - Marcseková, Klaudia; Wegener, Bernd; Doye, Sven (European journal of organic chemistry, 2005)
Abstract: We describe a very simple hydrogenation-like experimental protocol for the addition of gaseous methyl- and ethylamine to alkynes in the presence of Ind2TiMe2 as the catalyst. For efficient hydroamination reactions it is sufficient to stir a mixture of the alkyne and the catalyst in toluene at temperatures between 80 °C (terminal alkynes) and 105 °C (internal alkynes) under a constant pressure of 1 atm of the corresponding amine. After subsequent reduction of the initially formed imines, methyl- and ethylamine derivatives are the final products of the described one-pot reaction sequences. In the case of 2-alkyl-1-phenylalkynes as starting materials, biologically interesting 2-phenylethylamine derivatives possessing a small methyl or ethyl substituent at the N atom are easily accessible by the new reaction protocol.
Gesehen am 21.03.2018